MILIVOJE JOVANOVIĆ (1905 – 1984) ASSOCIATE OF THE OCCUPIERS AND/OR ASSOCIATE OF THE COMMUNIST PARTY OF YUGOSLAVIA APPENDICES FOR THE STUDY OF BIOGRAPHY (Heritage, 2023)
The paper analyses the biography of Milivoje Jovanović (1905 - 1984), a police officer, who for over 19 years performed various police administrative duties in Belgrade.At the beginning of the Second World War in Yugoslavia, he was the head of the General Police, and after the occupation he accepted collaboration in the new reorganization of the Belgrade City Administration. He was appointed as the head of the Special Police Department, which primarily dealt with the arrests and investigations of communists. He remained in this position until July 1941, after which he was transferred to the Inspector's Department, where he remained until March 1944.A less known fact from his biography is that before and during the Second World War, he helped some communists to avoid punitive raids or freed them from prison sentences. Thanks to the material provided to us by Milivoje Jovanović's family, we have tried to clarify this segment of his work in this article.The research showed that Milivoje Jovanović really had a decisive role in helping some communists, which is why he was spared by OZNA at the end of the war and was not qualified as a "collaborator of the occupiers".However, we should not forget his role and responsibility as a member of the Permanent Commission for the categorization of inmates in the Banjica camp, which sentenced many to death by firing squad. It should also not be forgotten that he was the head of the General Police at the time when the register of Jews was made by order of the Gestapo. For this reason, the role of Milivoje Jovanović during the Second World War is very complex and must not be analysed and evaluated unilaterally.
Keywords: ilivoje Jovanović, biography, Special Police, World War II, communists, collaboration